RAGAM METODE PENELITIAN KUANTITATIF DALAM KAJIAN MANAJEMEN DAKWAH: ANALISIS KONSEPTUAL DAN IMPLEMENTASINYA - Azizah, Anis Nadhja; Sarwoko, Edy; Jumi, Jumi; Kristyadi, Yapan; Sobirin, Sobirin (STKIP Subang, 2026)
The development of da’wah in the modern era demands professional, systematic, and data-driven management in response to increasing societal complexity and advancements in information technology. This article aims to conceptually examine various quantitative research methods relevant to da’wah management studies and to explain their implementation in academic research. This study employs a descriptive qualitative approach using a library research method and descriptive-analytical analysis of relevant scientific literature. The findings indicate that quantitative methods such as surveys, experiments, correlational studies, and ex post facto designs play an important role in measuring and evaluating the effectiveness of da’wah programs in an objective and structured manner. Survey methods are used to identify perceptions, satisfaction, and participation of congregants; experimental methods to test the effectiveness of da’wah strategies; correlational methods to analyze relationships among variables within da’wah organizations; and ex post facto methods to evaluate completed programs. The implementation of quantitative methods in da’wah management functions includes planning, organizing, actuating, and controlling, thereby supporting data-driven decision making. This study concludes that the use of quantitative methods can enhance the quality of da’wah management studies to become more systematic, objective, and evidence-based.